Office Planning and Design - Saphier Michael (Mcgraw Hill Book Company, 1968)
Introduction, Yesterday, Understanding, The Operational Aim, The Aesthetic Goals, The Financial Limitations, Analyzing, The Amount of Space Required, The Direction: Rent and Build or Remodel, A Program for a New Building, Exploring, Space Use, The Budget, Design, Preparing, A Design Preparation, Working Drawings, A Purchasing Program, Coordinating, The Bidding, The Building, The Moving, Planning for Design, The Practice, Of Office Practice, Organizing the Company, Personnel, Procedures, Philosophy, Tomorrow, Illustrations, Index.
Introduction, Yesterday, Understanding, The Operational Aim, The Aesthetic Goals, The Financial Limitations, Analyzing, The Amount of Space Required, The Direction: Rent and Build or Remodel, A Program for a New Building, Exploring, Space Use, The Budget, Design, Preparing, A Design Preparation, Working Drawings, A Purchasing Program, Coordinating, The Bidding, The Building, The Moving, Planning for Design, The Practice, Of Office Practice, Organizing the Company, Personnel, Procedures, Philosophy, Tomorrow, Illustrations, Index.